The Big 5 Personality Traits And Its Relation With Creativity - SARMA, DR. ASHA; BOROOAH, INDRANEE PHOOKAN (The journal of contemporary issues in business and government, 2021)
Creativity has been acknowledged as one of the predominant factors influencing individual’s contribution in various domains of life. History shows, that creative people possess unusual traits which make them different from their less creative counterparts. The present study was carried out on a group of reputed creative persons (national award winners) in the field of performing arts, visual arts and innovators in the area of science and technology. The total sample size is 180 (50 performing artists, 50 visual artists, 30 innovators, and 50 corporate executives which constituted the control group) aged between 30-65 years. For this purpose Standard Progressive Matrices developed by Ravens (1996) was used for screening purpose, in addition to the NEO-FFI-3 (Costa and McCrae, 1992) which was used to assess the Big 5 personality areas of openness to experience, conscientiousness, extraversion, agreeableness and neuroticism. To achieve the objectives Mean, SD, Kruskal Wallis ‘H’ test followed by Maan- Whitney ‘U’testwere the statistical tests used. Finally discriminant analysis was applied to strengthen the predictive validity of the test. Results yielded that out of the three creative groups, innovators were found to have a significantly higher mean value on openness to experience and conscientiousness, performing artists were found to have a significantly higher score on extraversion and agreeableness while visual artists were found to score high on neuroticism. Finally, openness to experience was found to be the most discriminating factor between the creative and the less creative (corporate executives).